(untitled) (International Journal of Physiotherapy, 2017)
Background: Compliance depends on the caregiver and the health care professional committing to the same objectives.Compliance with the prescribed physical therapy (PT) home program is a significant contributor to treatment success. Methods: One hundred caregivers were invited to fill in a questionnaire after the explanation of the procedure, and signing the consent form. The questionnaire explored factors affecting compliance including nature of the exercise, physical and emotional stresses on the caregiver, and the role of PT in teaching and counseling the caregiver. Result: Ninety-one participants out of the 100 were committed to administering the exercises with their children. Despite this, there was a discrepancy in either the frequency of repeating the exercises per day or the content of the exercise program when compared with the exercise program prescribed by the therapist. Some of the primary reasons for these differences were the pain experienced by the child when exercising (71%), having other family commitments (57%), not having the time to administer the home program (37%), and lacking skills or equipment to administer the exercises (34%). Conclusion: Adherence to treatment is a complex act that requires an understanding of treatment approach, having the confidence in one’s skills to administer the unsupervised home program and the existence of a support system both in the hospital and at home that can provide aid when needed. It is the PT role to address all these issues when prescribing a home program to meet treatment objectives.